Ghana : 2005 External Review of Public Financial Management, Volume 2, Annexes - World Bank (Washington, DC, 2012)
The 2005 External Review of Public Financial Management (ERPFM) consists of two volumes. The first volume is the main text, while the second volume comprises statistical annexes. In the first chapter of volume I, after this introduction, macroeconomic developments are assessed, including aggregate fiscal discipline and the risks to the fiscal outlook and macroeconomic stability. The next chapter focuses on budget management and the Ghana Poverty Production Strategy (GPRS). After a brief review of recent revenue trends, public expenditure management (PEM) is assessed in more detail through examining budget predictability and reliability and the implications for the strategic resource allocation role of the budget and the operational efficiency of public spending. The extent of alignment of the budget with GPRS is also reviewed. Finally, challenges to improving public expenditure management are discussed. The last chapter examines accountability issues through an assessment of the progress in implementing the new regulatory framework for public financial management, including the Financial Administration Act, the Public Procurement Act and the Internal Audit Agency Act, as well as the Budget and Public Expenditure Management System (BPEMS) and Integrated Personnel and Payroll Database (IPPD) systems. Volume II presents three annexes with information complementing the analysis of the main report and a Statistical Annex